Kualitas Rendang Daging Kambing dengan Penambahan Irisan Bawang Batak (Allium chinense G. Don) Ditinjau dari Kadar Protein dan Kadar Lemak - Nur Asmaq; Kabul Warsito (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2023)
This research aims to determine the quality of lamb rendang by adding sliced Batak onions (Allium chinense G. Don) to make it. The materials used in this research were lamb, Batak onions, chilies, shallots, garlic, galangal, ginger, turmeric, lemongrass, turmeric leaves, bay leaves, lime leaves, coconut, and salt. The method used in this research was an experimental method with a completely randomized non-factorial design with four treatments and four replications. The parameters tested were the lamb rendang's protein and fat content. The treatments in this study were P0 (control/rendang without adding Batak onions), P1 (addition of 5% Batak onion slices/meat weight); P2 (accumulation of 10% Batak onion slices/weight of meat), P3 (collection of 15% Batak onion slices/weight of heart). This study showed that the addition of sliced Batak onions in making rendang had a significant effect (P<0.01) on lamb rendang's protein and fat content. The protein content in the P3 treatment showed a value of 29.51%, while the fat content in P3 was 15.38%.